Stocking density, restricted trough space, and implications for sheep behaviour and biological functioning - Mayes, Bonnie T.; Tait, L. Amy; Cowley, Frances C.; Morton, John M.; Doyle, Brendan P.; Arslan, Muhammad A.; Taylor, Peta S. (Frontiers in Veterinary Science, 2022)
Stocking density and trough space allowance can potentially impact sheep welfare during live export voyages. The aim of this study was to assess the welfare implications for sheep housed at five allometric stocking densities, with either unrestricted or restricted trough space allowance. Merino wethers (n = 720) were housed in 40 pens of 18 heads for 18 days. Two 5-min continuous focal animal observations (n = 3/pen) were conducted on days 3, 5, 11, and 17. Scan sampling of standing and lying behaviours were conducted on the same days at hourly intervals. Live weights and immune cell counts were quantified at the start and end of the experiment, as well as faecal glucocorticoid metabolites (FGCMs), which were also assessed on days 6 and 12. Focal animals housed at higher stocking densities spent less time lying during one of the continuous observation periods, but no important effects on the overall number of animals lying or on the synchronicity of lying were evident. The scan sampling results indicated that the expression of some preferred lying positions was impaired at high stocking densities, and that high stocking densities also resulted in increased agonistic social interactions and displacement events at the start of the trial. There was a slight reduction in day 18 live weights for animals housed at higher stocking densities, but FGCM concentrations and immune cell counts were essentially unaffected. Trough space had no important effects on day 18 live weight, FGCM concentrations, or immune cell counts, and had limited effects on sheep behaviour. The lack of important impacts on biological fitness traits suggests that the behavioural responses observed were sufficient in allowing sheep to cope with their environment. However, we provide evidence that the provision of additional space is beneficial in reducing the time it takes for animals to adapt to their environment and to facilitate the expression of some preferred lying positions. While designed to emulate certain conditions relevant during live export voyages, some factors that may induce stress during this mode of transport were not present such as heat and ocean swell, so the conclusions must be interpreted in the context of the experimental conditions.